2012
DOI: 10.7314/apjcp.2012.13.6.2873
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Clinical Significance of STAT3, P-STAT3, and VEGF-C in Small Cell Lung Cancer

Abstract: The gene encoding STAT3, which is located on chromosome 12, consists of 750 to 850 amino acids and has a molecular weight of 84-113 kDa. STAT3 can be activated in three ways, namely, via the JAK-Stat way, Ras-MAPK approach, and size-independent enzymatic activation. Among them, the classic one is the Stat3 JAK-Stat way of signaling and transcription. In a number of cytokines and growth factor stimulators, STAT3 activates tyrosine or serine kinase

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
43
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 15 publications
2
43
1
Order By: Relevance
“…In fact, a compound with the ability to block the metastasis-associated steps could be a potential candidate for cancer chemoprevention and chemotherapy. It has been reported that the activation of STAT3 modulates the transcription of a variety of genes involved in the regulation of metastasis process, including ICAM-1 (Senggunprai et al, 2013) and vascular endothelium growth factor (Zhao et al, 2012). In this study, it was found that IL-6 increased the motility of CCA cells, and the specific JAK inhibitor, AG490, significantly decreased IL-6-dependent cell migration.…”
Section: Discussionmentioning
confidence: 50%
“…In fact, a compound with the ability to block the metastasis-associated steps could be a potential candidate for cancer chemoprevention and chemotherapy. It has been reported that the activation of STAT3 modulates the transcription of a variety of genes involved in the regulation of metastasis process, including ICAM-1 (Senggunprai et al, 2013) and vascular endothelium growth factor (Zhao et al, 2012). In this study, it was found that IL-6 increased the motility of CCA cells, and the specific JAK inhibitor, AG490, significantly decreased IL-6-dependent cell migration.…”
Section: Discussionmentioning
confidence: 50%
“…Drug resistance is one of the most important reason for failure of SCLC treatment (Chen et al, 2012). Therefore, understanding of the molecular and biological mechanisms of SCLC would contribute to the development of new treatments (Zhao et al, 2012). Improved long-term survival has been observed through combined modality therapy in LS-SCLC (Turrisi et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al (2012) studied about the expression levels of STAT3, P-STAT3, and VEGF-C in SCLC, and they found that the level of these markers higher than in normal tissue (p<0.05). They also showed positive correlations with clinical stage, tumor size, and lymph node metastasis (p<0.05).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations